The potential role of health impact assessment in tackling the complexity of climate change adaptation for health - Brown, Helen; Proust, K.; Spickett, Jeffery; Capon, A. (Australian Health Promotion Association, 2011)
Managing an issue of the magnitude, scope and complexity of climate change is a daunting prospect, yet one which nations around the world must face. Climate change is an issue without boundaries - impacts will cut across administrative and geographical borders and be felt by every sector of society. Responses to climate change will need to employ system approaches that take into account the relationships that cross organisational and sectoral boundaries. Solutions designed in isolation from these interdependencies will be unlikely to succeed, squandering opportunities for long-term effective adaptation. Health Impact Assessment (HIA) provides a structural approach to identify, evaluate and manage health impacts of climate change that is inclusive of a wide range of stakeholders. Climate change will affect decision-making across every government level and sector and the health implications of these decisions can also be addressed with HIA. Given the nature of the issue, HIA of climate change will identify a large number of variables that influence the type and extent of health impacts and the management of these impacts, In order to implement the most effective adaptation measures, it is critical that an understanding of the interactions between these variables is developed. The outcome of HIA of climate change can therefore be strengthened by the introduction of system dynamics tools, such as causal loop diagrams, that are designed to examine interactions between variables and the resulting behaviour of complex systems.